Humoral and cellular immune response dynamics in Japanese healthcare workers up to six months after receiving a third dose of BNT162b2 monovalent vaccine. Issue 9 (24th February 2023) - Uwamino, Yoshifumi; Yokoyama, Takashi; Sato, Yasunori; Shibata, Ayako; Kurafuji, Toshinobu; Tanabe, Akiko; Noguchi, Masayo; Arai, Tomoko; Ohno, Akemi; Yokota, Hiromitsu; Namkoong, Ho; Nishimura, Tomoyasu; et al.
Highlights: This prospective cohort study assessed immune response to the BNT162b vaccine. Participants were followed up from pre-vaccination to 6 months after the 3rd dose. Immunity 6 months after the 3rd dose was similar to that 8 weeks after the 2nd dose. The 3rd dose produced a more durable immune response than the 2nd dose. Abstract: Longitudinal data on the immune response from the first dose to several months after the third dose of COVID-19 vaccine are limited. We analyzed the immune response in 406 Japanese healthcare workers who received at least three doses of vaccine. The geometric mean anti-receptor binding domain IgG antibody titers and antigen-stimulated T -cell interferon-gamma levels after 6 months after receiving a third dose were similar to those 8 weeks after receiving a second dose. Humoral and cellular immunity induced by the third dose was more durable than that induced by the second dose. UMIN Clinical Trials Registry ID: UMIN000043340.